Pengaruh Net Profit Margin (NPM) dan Return on Assets (ROA) Terhadap Price Earning Ratio (PER) - Andri Susilo; Nur Sapitri (Universitas La Tansa Mashiro, 2022)
Investment is a commitment to a number of funds made at this time, with the aim of taking advantage of the current increase in stock prices in the hope of obtaining profits in the future. Price Earning Ratio (PER) is information that is both fundamental and technical. The use of this model becomes very important to assess stock prices and help investors in planning and deciding investments effectively. This study aims to determine the effect of Net Profit Margin (NPM) and Return On Assets (ROA) on Price Earning Ratio (PER) either partially or simultaneously in banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 - 2020. The method used in this study is a quantitative research method with a descriptive analysis approach. The total population in this study were 46 companies and after selecting the sample using purposive sampling technique, 24 companies were obtained which will be used as samples in this study. The type of data used in this research is secondary data. The data analysis model used in this research is using the prerequisite test of data analysis which includes: normality test, multicollinearity test, autocorrelation test, heteroscedasticity test. The hypothesis test used in this study includes: multiple regression analysis, correlation analysis, coefficient of determination, t test, and f test. Based on the data analysis, it can be concluded that the Net Profit Margin (NPM) partially has no effect and is not significant on the Price Earning Ratio (PER). Meanwhile, Return on Assets (ROA) partially has no effect and is not significant on the Price Earning Ratio (PER). And simultaneously (together) Net Profit Margin (NPM) and Return On Assets (ROA) have a significant and significant effect on Price Earning Ratio (PER).